Bank partnership and liquidity crisis - CHOI, Seungho (Institutional Knowledge at Singapore Management University, 2020)
This study empirically investigates the relationship between banking integration and liquidity management. To measure banks’ connectivity, we use the number of partnerships proxied via the syndicated loan arrangements in which they serve as lead arrangers. If banks establish more business partnerships through syndicated loan arrangements, those under market stress are more likely to face increased funding costs, create reduced liquidity, and originate declined small business loans and mortgages. Those banks with more partners are shown to have a lower liquidity coverage ratio, suggesting that business partnerships create a disincentive toward liquidity risk management.